PENINGKATAN MINAT WIRAUSAHA MELALUI MODEL SINEKTIK PADA SISWA KELAS AK2 DI SMK N 1 WINDUSARI MAGELANG - murdiyanto, ari (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2022)
Abstrak: The main objective of the research is to improve students’ entrepreneurial interest at grade XII AK 2 in SMK N 1 Windusari Magelang using synectic model. The method of the research is classroom action research. The object of the research is 31 students at grade XII AK 2 in SMK N 1 Windusari Magelang. The data is collected using observation and interview. The instrument of the data is entrepreneurial interest scale. The result of validity test using entrepreneurial interest scale is 36 of 48 items is valid which covers the indicators entrepreneurial interest scale. In addition there are 12 items which is invalid item. The test reliability of the instrument coefficient is 0.820 which has a high level of reliability. Technique of analysis data is quantitative descriptive. The procedures used in this research are preparing instrument, testinginstrument used pre-test entrepreneurial interest, and implementing synectic model used game. Synetic model activity is carried out in two cycles which each cycle has one cycle activity. The research finding shows that synectic model is able to improve students’ creativitydevelopment and problem solving. The result of object pre-test and post-test II has improved entrepreneurial interest. Pre-test result is 68.74, after implementing syntetic model, the result of the post test is improved 121.90. Comparing the result of pre-test and post-test, it has improved 78.39 %. It shows that applying synectic model using game is able to improve entrepreneurial interest.